Decrease in chemical demand of oxygen (cod) in waste water of generated in an agrochemical industry - López Rocafuerte, Franklin; Fierro Aguilar, Jaime; Calero Córdova, René (Revista Universidad de Guayaquil, 2015)
Through a procedure of primary type for the treatment of wastewater containing pesticides, herbicides and other substances, determined the type of oxidizing more suitable for lower chemical demand of oxy gen (COD) in these waters, which are within the parameters required by the environmental authorities for later download.chemical oxygen demand (COD) in these waters, the same that are within the parameters required by the environmental authorities for later download. The research was conducted considering the importance of establishing methodologies for application in industry that operates such products; it is not unknown that pollution currently represents a very serious problem for community and ecosystem consequences as well-known as its global impact This study used an experimental method, which initially consist ted of the application of a preliminary or primary, treatment followed by a secondary treatment. Together,it was used as part of the xperimental process, final treated water aeration Consequently, demonstrate the reduction of organic load through the use of a suitable oxidant, and also that each wastewater that is generated in the industry has its own characteristics, therefore must select the most appropriate treatment method.
Keywords: Treatment; wastewater; pollution; aeration; loading; loading organic; oxidizing